Шляхи підвищення ефективности державного фінансового аудита - Ломаченко, Т.И. (Культура народов Причерноморья, 2013)
Проведен анализ организации и методики проведения различных видов государственных
аудитов, эффективности системы государственного финансового контроля, в частности
государственного аудита Украины. Автором обоснованы системы мер контроля государственных
финансов на основе новейших технологий обработки финансовых данных.
Ключевые слова: управление государственными финансами, государственный аудит, эффективная
система управления аудита, методы организации контроля, планирование, риск. Здійснено аналіз організації та методики проведення різних видів державних аудитів,
ефективності системи державного фінансового контролю, зокрема державного аудиту України.
Автором обгрунтовані системи заходів контролю державних фінансів на основі новітніх технологій
обробки фінансових даних.
Ключові слова: управління державними фінансами, державний аудит,ефективна система управління
аудиту, методи організації контролю, планування, ризик. The analysis of the organization and methods of the various types of government audits, the
effectiveness of the system of state financial control, in particular the state audit of Ukraine, is conducted. The
author grounded the system of public finance control measures that based on the latest technologies for
processing financial data, creating conditions for the professional and educational level of auditors to ensure
the effective performance of its tasks.
The analysis of the effectiveness and efficiency of internal standards and procedures for state financial audit and
information-analytical system of state finance is provided, which contain one of the important stages of
improving approaches to planning financial control through the selection of objects for monitoring.
Questions of improvement anti-corruption legislation and control over compliance legislation on conflict of
interest is grounded, as well as the introduction of additional mechanisms to prevent and combat corruption.
Key words: management of government finances, government audit, effective system of the audit management,
methods of control, planning, risk.